Scoping Review & Perspektif : Business Ethic From Entrepreneur On SMEs - Risca Kurnia Sari; Sudarmiatin Sudarmiatin; Satria Putra Utama (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Various problems related to today's business ethics have increasingly developed with the emergence of easy access to available social media. The spread of ethical issues in business can significantly affect the quality and popularity of a company. The application of good business ethics will certainly help the company to be able to continue to survive and advance in the current era of increasingly inadequate technology. The purpose of this study is to describe how business ethics should exist in a company. This scoping study aims to examine the literature regarding the most relevant and significant aspects of business ethics in entrepreneurship, as well as the methods used in related research. This study searches multiple databases for articles published between 2012 and 2023. The results of the study show that the contribution of business ethics is needed to improve the quality of company development. The existence of the application of good business ethics will help the company achieve its vision and mission in accordance with what is expected.